To oblivion and beyond: Imagining infrastructure after collapse. (December 2020) - Carter, Daniel; Acker, Amelia
Theorists of infrastructure have thought a great deal about time and temporality but have not often seriously considered the future of these massive and durable objects. This elision is notable due to infrastructures' current role in our world: highly vulnerable to crises such as those brought about by climate change yet also playing a role in hastening such events. Following Lauren Berlant and Dominic Boyer, we take the current moment as an opportunity to reconsider infrastructure and to work toward a perspective that would see it as a resource from which to construct more creative and equitable futures. Here, we consider such futures through readings of Kim Stanley Robinson's Three Californias Trilogy, which imagines various sociopolitical futures for southern California. Attending to the roles that infrastructures play in shaping these futures, we argue for a perspective that sees collapse as an opening of material possibility and highlight aspects of infrastructures, such as their distribution in space that might prove meaningful in thinking about such crises and transitions.